PROBLEMATICS OF KAFA'AH IN AS-SYAFI'IYYAH REGULATION LAW PERSPECTIVE - Abdul Gofur; Islah Abdurrahman (al-Rasῑkh: Jurnal Hukum Islam, 2022)
Discussing the Kafa'ah Problems in Shari'ah Law is motivated by the importance of understanding kafa'ah in society because some of these communities focus on education and wealth. And it would be more fortunate in a marriage if the community prioritizes religion, it will be able to create a happy family. The history of marriage is a matter that Allah has permitted and has prescribed through the mouth of His Messengers, in which there are worldly and hereafter benefits.